2011
DOI: 10.1002/clen.201100248
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Stream Water Quality during Snowmelt and Rainfall – Runoff Events in a Small Agricultural Catchment

Abstract: Surface water quality can vary a lot with fluctuating discharge during a Rainfall -runoff event. This paper uses a set of hydrological and hydrochemical variables to explain concentration-discharge loops and hysteresis of NO À 3 , NH þ 4 and total suspended solids in a brook dewatering a small upland agricultural catchment in the Czech Republic. Our study is based on data collected by a continuous monitoring approach provided by an automatic ISCO sampler both from snow thawing and rainfall -runoff events. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…reduced the NO 3 ‐N concentration, depending on which part of the hydrograph limb (ascending or descending) was recorded at the moment of sampling. At the beginning of the ascending limb the concentrations increased, but with further growth of flow rates they decreased and were diluted, which has been described also by . The several‐fold increased flow rate during the episodes meant that, even at lower NO 3 ‐N concentration, the solute load was much higher than that in baseflow periods, when NO 3 ‐N concentration was higher, namely in spring.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…reduced the NO 3 ‐N concentration, depending on which part of the hydrograph limb (ascending or descending) was recorded at the moment of sampling. At the beginning of the ascending limb the concentrations increased, but with further growth of flow rates they decreased and were diluted, which has been described also by . The several‐fold increased flow rate during the episodes meant that, even at lower NO 3 ‐N concentration, the solute load was much higher than that in baseflow periods, when NO 3 ‐N concentration was higher, namely in spring.…”
Section: Resultsmentioning
confidence: 67%
“…During some of the events captured in the presented study, the NO 3 ‐N concentrations grew significantly, along with increasing P concentrations (in the ascending limb). However, in other events, the new water probably expelled the old water, or partly mixed with it, which in relation to the nature (quantity and intensity) of water runoff, season and watershed condition (saturation of the soil profile) caused the primary increase of NO 3 ‐N concentrations in both drainage and surface waters and, conversely, null or slow (or at least not dramatic) increase of P concentration . For both phosphorus forms, both in Q b and Q tot , the C – Q relationships described by regressions were rather weak (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…Future work could focus on the linkages between catchment characteristics, nutrient load dynamics, and load calculation uncertainties provided by different methods in different seasons. Further, a more detailed hydrological description of the sites such as runoff flashiness, baseflow index, antecedent moisture conditions, or water catchment residence time will be employed in a follow-up study in order to better explain the magnitude of uncertainty and the dynamics of various algorithms across different catchments [27,34,46,47]. Author Contributions: Petr Fučík, Antonín Zajíček, and Renata Duffková conceived and designed the experiments; Antonín Zajíček, Jana Peterková, Petr Fučík, Renata Duffková, and Markéta Kaplická performed the experiments; Antonín Zajíček, Markéta Kaplická, Petr Fučík, Renata Duffková, Jana Peterková, and Jana Maxová analyzed the data; and Petr Fučík, Antonín Zajíček, Markéta Kaplická, Renata Duffková, and Šárka Takáčová wrote the paper.…”
Section: Discussionmentioning
confidence: 99%
“…This connectivity is affected by the position of a drainage system in a particular part of a slope (higher, lower) and by local soil variability [42,43,[47][48][49]. This can lead to different proportions of runoff components in drainage runoff, e.g., sites lying in higher positions on slopes (typically P53) have lower proportions of baseflow and higher numbers of REs.…”
Section: Runoff Events and Their Proportion On Total Runoff N And P mentioning
confidence: 99%
“…Research focused on nitrogen leaching from arable land attempts to find potential ways to reduce fertilization, use intercrops or winter crops and changes in land parcel types, promote changes in agro-technology (tillage) in selected catchment zones, or use combination of these techniques while maintaining crop yields. In general, there is a significant seasonal and inter-annual variability in the nitrogen leaching, with the main determining factors represented by the weather course (precipitation, temperature, soil moisture), accumulated nitrogen content in the soil, and intensity of its mineralization (Bauwe et al 2015, Fučík et al 2012). Fučík, Novák & Žížala (2014) and Fučík et al (2015) have shown that nitrogen leaching from agricultural land can be reduced by targeted grassing in the areas at risk of accelerated infiltration.…”
Section: Introductionmentioning
confidence: 99%